Plan de marketing Digital para la empresa LOVI en la ciudad de Loja - Jiménez Villalta, Ricardo Leonel (2024)
The research seeks to analyze the external and internal situation of the company in search of the opportunities and threats of the environment in which the company interacts and also to identify the strengths and weaknesses that the company has. The objective of all of them is to be able to make digital marketing strategies from all that information. Therefore, for the development of the study, information was collected on the tastes and preferences of current and potential customers, carrying out two types of surveys directed specifically to each group, so a total of 383 surveys were applied to potential customers and 22 surveys for current customers, all results were analyzed through IBM SPSS 22, revealing important information that helps the development of strategies. The results of the research revealed that the company still needs to improve in many aspects and one of them is in the area of marketing and sales, which is why all the strategies developed from the SWOT are focused on improving the company to position itself in the market and in the mind of the consumer and above all to grow, considering strategies such as content creation, active presence in social networks, participation in events, etc. All these strategies are part of a marketing plan designed especially for the company to achieve its desired objectives.